Pemberdayaan Usaha Sentra Ikan Asin Melalui Sosialisasi Pelatihan Digitalisasi bagi Kelompok Usaha di Seberang Ulu 1 Kota Palembang - Wahidin Wahidin; Dwi Muhammad Taqwa (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
One type of business that remains consistent and develops to meet community needs is the salted fish production business which is managed traditionally. As all types of businesses develop nowadays, market competition becomes increasingly fierce, so this situation forces business actors to try to optimize the processing of quality salted fish production and try to make new breakthroughs in the marketing of salted fish through digitalization. Technological advances or digitalization are currently one of the potentials that can be utilized by business actors as a promotional tool in increasing the productivity of salted fish businesses to the global market. Digitalization is one of the information technologies that is currently widely used for business activities and has the potential to be a means of business promotion through social media, which is considered very effective in encouraging business actors to develop further. This socialization activity was attended by 20 UKM participants (twenty people) who are members of the Palembang Salted Iwak Center (SIABANG) community in Lima Ulu Village, Palembang City. The aim of this activity is to motivate salted fish business actors to put into practice the knowledge they gained during training and be able to make product packages in packaging that are suitable for sale. The business actors were very enthusiastic in participating in the socialization and digitalization training activities delivered by the presenters. Conditions like this can motivate salted fish business actors to remain enthusiastic about selling their products so that their businesses can progress further into the global market.